Board Diversity dan Kualitas Laba: Studi pada Perusahaan Manufaktur di Indonesia - Irwansyah, M. Rudi; Vijaya, Diota Prameswari; Tripalupi, Lulup Endah (Universitas Pendidikan Ganesha, 2020)
This study aims to determine the effect of board diversity which includes gender diversity, foreign diversity and age diversity partially and simultaneously on the earnings quality in manufacturing companies listed on the Indonesia Stock Exchange. Later, this study provide the importance of the diversity of the board of directors in the company. Sample in this research is manufacturing companies listed on the Indonesia Stock Exchange in 2018 using a purposive sampling technique. The number of samples in this research were 150 companies. Analysis of the data in this research using multiple regression analysis. The results showed that gender diversity, foreign diversity, and age diversity had no effect either partially or simultaneously on the quality of company earnings. This is because the irrational proportion of the board of directors as the cause of the insignificant influence of gender, foreign nationality and board of directors age 40-45 on earnings quality.